Assessing body composition in rugby players: agreement between different methods and association with physical performance - Hartmann Nunes, R. F.; de Souza Bezerra, E.; Orssatto, L. B.; Moreno, Y, M.; Loturco, I.; Duffield, R.; Silva, D. A.; Guglielmo, L. G. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: This study investigated the comparability between air displacement plethysmography (ADP), dual-energy X-ray absorptiometry (DXA), and bioelectrical impedance analysis (BIA) methods for body composition assessment and their correlations with physical performance in rugby players. METHODS: Nineteen male elite players participated in the study. ADP, DXA, and BIA were used to assess fat-mass and fat-free mass. Physical performance was assessed by means of Carminatti`s test of peak velocity (PVTCAR), countermovement jump (CMJ), sprint speed (10 and 30-m), and match performance analyses (sprinting, distance covered, and high-intensity running). RESULTS: BIA overestimated fat-mass (13±41%; r2=0.60) and underestimated fat-free mass (-1±7%; r2=0.66) compared to ADP (P=0.001). BIA underestimated fat-mass (-28±3%; r2=0.92) and overestimated fat-free mass (10±5%; r2=0.87) compared to DXA (P<0.001). ADP underestimated fat-mass (-36±37%; r2=0.69) and overestimated fat-free mass (11±8%; r2=0.52) compared to DXA (P<0.001). Fat-mass measured by ADP, DXA, and BIA negatively correlated with PVTCAR (r2=0.49), height and peak power from CMJ (r2=0.30), sprinting ability (r2=0.65), and match performance variables (r2=0.30). CONCLUSIONS: As long as one considers that ADP and BIA underestimated fat-mass and overestimated fat-free mass compared to DXA, the methods can be used to estimate body composition, particularly to track body fat-mass changes, which negatively influence several physical capacities determinant to rugby performance. The limitations of the methods should be borne in mind when assessing the body composition of rugby athletes.